EVALUASI IMPLEMENTASI PERANGKAT LUNAK E-INVOICE PADA DIVISI FINANSIAL MENGGUNAKAN DELONE & MCLEAN IS SUCCESS MODEL (STUDI KASUS : PT XYZ) - Amy Aisya; Debbie Amalina (UNUSA Press, 2021)
E-Invoice considered as one of the most implemented financial information systems these recent years. E-Invoice had grown from a system that brings convenience, into a part of the strategy to fulfill corporate expectation. However, it’s uncertain whether E-Invoice implementation indeed successfully brings proven benefits into the company business, especially in mandatory environment. Therefore, the aim of this study is to identify the indicators that affect the success of E-Invoice implementation in a particular state-owned company, based upon DeLone & McLean IS Success Model which adjusted to fit mandatory environment. In terms of evaluation, previous research regarding E-Invoice mostly discussed about the key factors that influence the adoption of E-Invoice. Therefore, most of the evaluation using DeLone & McLean IS Success Model did not consider the environment of the system. This research also examining whether the mandatory-environment-adjusted DeLone & McLean IS Success Model is valid for evaluating IS success. According to DeLone & McLean IS Success Model, there are six variables used as basic measurement, namely information quality, system quality, service quality, user satisfaction, intention to use, and net benefits. Following that, a set of structured questionnaire arranged and distributed to 34 users of an E-Invoice system provided by a state-owned enterprise headquartered in Rembang, Indonesia, which are vendors. The data then will be processed using Partial Least Square (PLS) method. The result showed that Information Quality and System Quality gave significant impact to User Satisfaction and User Satisfaction has the most impact towards Net Benefits.